Fuzzy TOPSIS method as a decision supporting system to rank Malaysia online shopping website quality during COVID-19 MCO 2020 - Fam, Soo-Fen; Huang, Joshua; Chuan, Zun Liang; Siti Nurhaida, Khalil; Dedy Dwi, Prastyo; Fatin Najwa, Mohd Nusa (World Academy of Research in Science and Engineering, 2020)
The rapid growth of Internet technology development has allowed consumers to purchase online products or services, especially during the Movement Control Order (MCO) lockdown due to the COVID-19 pandemic in Malaysia. Online shopping has become a new norm; however, the services needed frequent updates for improvements. Literature has shown that online shopping website quality influenced online shoppers’ decision-making. Hencein improving the quality of online shopping websites, the criteria for the website’s quality is vital. Therefore, this study aims to identify the criteria of Malaysia online shopping website quality and rank the website quality by using Fuzzy TOPSIS method. Questionnaire is developed for website usersto evaluate the online shopping website quality via google form and disseminated through social media. After data cleaning, 300 respondents’ data were used for analysis. The result shows that the online shopping website quality for Shopee is ranked the first, next is Lazada, then Lelong and finally the 11-street.